2004
DOI: 10.1128/aem.70.1.363-369.2004
|View full text |Cite
|
Sign up to set email alerts
|

Saturable, Energy-Dependent Uptake of Phenanthrene in Aqueous Phase by Mycobacterium sp. Strain RJGII-135

Abstract: The mechanism of uptake of phenanthrene by Mycobacterium sp. strain RJGII-135, a polycyclic hydrocarbondegrading bacterium, was examined with cultures grown on phenanthrene (induced for phenanthrene metabolism) and acetate (uninduced). Washed cells were suspended in aqueous solutions of [9-14 C]phenanthrene, and then the cells were collected by filtration. Low-level steady-state 14 C concentrations in uninduced cells were achieved within the first 15 s of incubation. This immediate uptake did not show saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…The low bacterial cell densities used in the present work resulted in passive sorption to the cells that was reduced compared to the level that was found in previous studies reporting nearly instantaneous sorption of PAH to bacterial cells and dissolved humic materials, with equilibration times of less than 1 min (3,8,27). This lower rate of passive sorption allowed us to observe profound differences between induced and uninduced cells in uptake rates.…”
Section: Discussionmentioning
confidence: 50%
“…The low bacterial cell densities used in the present work resulted in passive sorption to the cells that was reduced compared to the level that was found in previous studies reporting nearly instantaneous sorption of PAH to bacterial cells and dissolved humic materials, with equilibration times of less than 1 min (3,8,27). This lower rate of passive sorption allowed us to observe profound differences between induced and uninduced cells in uptake rates.…”
Section: Discussionmentioning
confidence: 50%
“…Different species differ in their ability to degrade different substrates and few organisms have the potential to degrade all available plant cell wall components. [43,44] Generally, micro-organisms adapted to use hydrophobic hydrocarbons, such as phytosterols, need to possess the following physiological properties: (1) lipophilic cell walls and adaptive changes in surface properties allowing direct adhesion to hydrophobic substrates, (2) high affinity uptake systems such as active transporters and membrane-associated enzymes for initial degradation, and (3) the ability to excrete biosurfactants or bio-emulsifiers to increase the bioavailability of phytosterols. Based on these properties, moulds are interesting biotransformation candidates as they are capable of adapting to different substrates, due to their parasitic nature and capability to produce a wide variety of extracellular enzymes.…”
Section: Speciesmentioning
confidence: 99%
“…In contrast, Whitman et al [95] proposed the involvement of a specifi c, energy-dependent transport system for incorporation of naphthalene in P. fl uorescens Uper-1. Miyayta et al [87] also suggested that both passive diffusion and a saturable transport system(s) may contribute to the utilization of phenanthrene by Mycobacterium sp. strain RJGII-135 in the aqueous phase.…”
Section: Transport Of Pahs Into the Cellmentioning
confidence: 99%
“…Such movement is generally brought about by passive transport down a concentration gradient from the environment into the cell [85][86][87]. Such transport, however, depends on a number of factors, crucial amongst which are concentration and the bioavailability of contaminants from the surrounding medium.…”
Section: Transport Of Pahs Into the Cellmentioning
confidence: 99%